Editors’ Introduction: Recognition, Dignity, and Lived Governance in Contemporary Asia - Asep Muhamad Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2024)
JASSR Vol. 6, No. 2 (2024) examines how people across Asia encounter power in everyday life and seek dignity within changing institutions. Moving from the Manipuri and Bishnupriya communities in Bangladesh to Benda Kerep village in Cirebon, from Indonesian Islamic higher education to narcotics law reform, from resettled rural workers in Vietnam to becak drivers’ views of Sharia enforcement in Aceh, the issue asks how identities are defended, traditions are adapted, gendered barriers are challenged, laws are reimagined, livelihoods are rebuilt, and religious regulations are judged from below. Together, the articles show that governance is not experienced only through formal policy, but lived through recognition, exclusion, adaptation, negotiation, and the everyday search for fairness.